KERALA WOMEN:LESS THAN EQUALS? - K. SARADAMONI
Women in Kerala, despite many indicators like favourable sex-ratio, literacy, access to education and health care are far from being equal members of the society. The state has witnessed many socio-political changes in the last hundred years. But the period seen as 'progressive' saw the building up of a genderedhierarchy, pushing women to a dependent status.